2004
DOI: 10.1128/jvi.78.19.10674-10684.2004
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytoplasmic Sequestration of the Nuclear Export Receptor CRM1 by NS2 Mutations Developed in the Host Regulates Parvovirus Fitness

Abstract: To investigate whether a DNA virus can evade passive immunotherapy with a polyclonal antiserum, we analyzed the protection of a neutralizing capsid antiserum against a lethal infection of the immunosuppressive strain of the parvovirus minute virus of mice (MVMi) in 42 immunodeficient mice over a period of 200 days. A few mice were effectively protected, but most developed a delayed lethal leukopenic syndrome during the treatment or weeks afterwards. Unexpectedly, viruses isolated from treated but also from con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…We found that the previously characterized NS2 mutation (14) which increases NS2-Crm1 interaction above wild-type levels could rescue ssDNA replication in fibroblasts in the MVMi background, in spite of the reduced levels of NS2 in these cells. NS2 mutants that generate wild-type levels of an NS2 protein that no longer interacts with Crm1 have multiple restrictions Marker lane contains double-stranded DNA fragments of (from bottom) 2.5, 5.0, and 7.5 kb.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…We found that the previously characterized NS2 mutation (14) which increases NS2-Crm1 interaction above wild-type levels could rescue ssDNA replication in fibroblasts in the MVMi background, in spite of the reduced levels of NS2 in these cells. NS2 mutants that generate wild-type levels of an NS2 protein that no longer interacts with Crm1 have multiple restrictions Marker lane contains double-stranded DNA fragments of (from bottom) 2.5, 5.0, and 7.5 kb.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, Lopez-Bueno et al isolated a group of MVMi mutants that were selected for the ability to escape passive immunotherapy in immunosuppressed mice (14). Interestingly, a number of these viruses contained muta- tions in NS2 that increased the affinity of NS2 with Crm1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations